Digital network composing practices: digital removal in the Try Guys media ecology - Banuelos, Mia, author; Amidon, Timothy R., advisor; Doe, Sue, committee member; Elkins, Evan, committee member (Colorado State University. Libraries, 2024)
With an increased accessibility and democratization of digital editing tools, recomposition has the potential to occur to any text or artifact circulated in a digital space. One form of recomposition that must further be considered is digital removal practices, including erasure, deletion, deflection, and exclusion of human or non-human objects in a digital composition. These practices have the potential to impact digitally networked composing practices and how we think about rhetoric and writing in media ecologies. This thesis focused on the intersection of digital removal practices and Ridolfo and DeVoss' theorization of rhetorical velocity, which considers composing for recomposition, and its co-influence on digitally network composing practices. Through a case study of The Try Guys, a group of popular YouTube personalities, this thesis explored the influence of a participatory culture in a media ecology and the role recomposition plays in a public scandal. Data was collected from The Try Guys media ecology surrounding the removal and/or revision of a former member, Ned Fulmer, and the larger medial ecology comprising The Try Guys' social media presence. These data illustrated the significant influence of participatory culture, as an influx of users associated with The Try Guys fandom contributed to the rhetorical velocity and recomposition of information and context produced by the Try Guys. Specifically, data illustrated that participatory cultures can and do shape how digital removal unfolds within and beyond digital networks. This thesis (1) emphasized the increased influence of a participatory culture on the curation and circulation of content in a media ecology and (2) explored how digital removal practices have the potential to influence how we theorize rhetorical velocity and how we must be strategic for composing as authors, writers, users, creators, inventors, teachers, and students.
Keywords: digital erasure; participatory culture; rhetorical velocity; digital removal; circulation; recomposition